A method for regulating element diffusion at the interface of PVD coating by laser shock
By laser impact strengthening the PVD coating, the problem of insufficient improvement of coating interface bonding performance and wear resistance is solved, and a gradient element distribution layer and nanogradient structure are formed, optimizing the surface quality and performance of the coating.
Patent Information
- Application Number
- CN202310807483.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-04
AI Technical Summary
After the PVD coating is strengthened, the interface bonding performance and wear resistance are not significantly improved, and the surface roughness is severely damaged. XRD phase analysis shows that the phase composition of the membrane-based interface has not changed, and there is a problem of heterogeneity of the membrane-based material.
By pretreating the substrate, a PVD coating is prepared, and the laser impact parameters are determined according to the parameters of the PVD coating, and the PVD coating is subjected to laser impact enhancement treatment, and the high temperature, ultra-high-speed stress strain and crystals generated by laser impact enhancement are used to utilize the high temperature, ultra-high-speed stress and strain and crystals generated by laser impact enhancement. Defects promote the diffusion and permeation of coating elements, form gradient element distribution layers, and optimize the binding performance and structural refinement of the coating interface.
Laser impact enhancement improves the interface bonding performance of PVD coatings, forms a nanogradient structure, refines grain structure to submicron or even nanoscale, changes phase distribution, and improves the surface quality and performance of the coating.
Smart Images

Figure CN116815134B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of laser enhanced shock technology, and specifically relates to a method for regulating the elemental permeation at the interface of a PVD coating by laser shock. Background Art
[0002] Laser shock peening is an advanced surface modification technology. It mainly uses short pulse, high peak power laser to irradiate metal target to induce plasma shock wave, which acts on the surface of the material as a direct force source, and then does not transmit into the material. When the peak pressure of the shock wave exceeds the dynamic yield strength of the material, the metal material undergoes plastic deformation and generates a certain residual compressive stress. Its strain rate can reach more than 106 / s, and the strain affects the layer depth, which can play a role in regulating the surface quality of the material and improving the surface performance of the material.
[0003] Laser impact physical vapor deposition coated metal material surface, due to the laser impact plastic flow effect, the material under the impact load flow to the inside, and form a nano gradient structure. In the absence of the protection of the absorption layer, due to the laser thermal effect and shock wave pressure, the material may form the diffusion of elements and phase change on the basis of plastic flow, and due to the laser ablation, defective phases may be formed, which also has a certain impact on the formation of nano structure, element distribution, and phase distribution gradient. Summary of the invention
[0004] The present application provides a method for regulating elemental desorption at the interface of a PVD coating by laser shock in order to solve the technical problems that the interface bonding performance and wear resistance of the coating after strengthening treatment are not significantly improved, the surface roughness is severely damaged, the phase composition of the membrane-base interface does not change according to XRD phase analysis, and there is heterogeneity of the membrane-base material.
[0005] In order to solve the above technical problems, a technical solution adopted in this application is: a method for regulating the elemental permeation at the interface of a PVD coating by laser shock, comprising:
[0006] Pre-treating the substrate based on the size of the substrate;
[0007] Based on the pretreated substrate, preparing a PVD coating on the pretreated substrate;
[0008] Based on the parameters of the PVD coating, the parameters of the laser shock are determined, and the PVD coating is subjected to laser shock strengthening treatment;
[0009] Based on the PVD coating after laser shock peening treatment, SEM and EDS characterization observations were carried out on the PVD coating.
[0010] Further, based on the size of the substrate, the method for pre-treating the substrate includes:
[0011] Based on the size of the substrate, the substrate is subjected to wire cutting processing to obtain a unit substrate;
[0012] Based on the unit substrate and sandpapers of different meshes, the unit substrate is polished step by step;
[0013] The unit substrate is cleaned by ultrasonic cleaning based on ethanol to obtain a pre-treated substrate.
[0014] Further, based on the pre-treated substrate, a method for preparing a PVD coating on the treated substrate comprises:
[0015] Based on the pre-treated substrate, arc ion plating and target materials are selected, and the pre-treated substrate and target materials are placed in a sample chamber;
[0016] Regulate the vacuum degree of the sample chamber and determine the arc-light bombardment cleaning parameters;
[0017] A deposition gas is introduced into the sample chamber, the ratio flow of the deposition gas is controlled to be 1:1, and the deposition time is 60 to 90 minutes to obtain a PVD coating;
[0018] Based on the deposited PVD coating, the pre-treated substrate was placed in a vacuum and 600°C heat treatment environment and the PVD coating was stress relieved.
[0019] Furthermore, the thickness of the PVD coating is 3 to 5 μm.
[0020] Furthermore, the vacuum degree of the sample chamber is less than 7×10 -3 Pa.
[0021] Further, based on the parameters of the PVD coating, the parameters of the laser shock are determined, and the method for laser shock peening treatment of the PVD coating includes:
[0022] Based on the laser equivalent peak pressure, the corresponding laser shock parameters are selected; wherein the laser shock parameters include laser energy, spot diameter and pulse width;
[0023] The PVD coating is laser-shocked based on the selected laser shock area and laser shock range.
[0024] Furthermore, before laser shock peening of PVD coating, the following steps are required:
[0025] Optical glass is used as a constraint layer in the laser shock strengthening area, and the laser shock range is in the absence of an absorption layer.
[0026] Furthermore, the overlap rate of laser shock peening is not less than 50%.
[0027] The beneficial effects of the present application are as follows: The present application studies the regulation of element diffusion and penetration at the interface of heterogeneous laser shock of PVD coating on the alloy surface based on the principle of laser shock strengthening. In the absence of the protection of the absorption layer, the high temperature, ultra-high-speed stress and strain generated during the laser shock strengthening process, and the induced crystal defects are utilized to promote the diffusion and penetration of the coating elements on the substrate surface on the basis of the plastic flow mechanism of laser shock strengthening, and to enrich and distribute them to a certain extent, forming a certain gradient element distribution layer. At the same time, laser shock strengthening optimizes the interface bonding performance of the PVD coating. On the one hand, the characteristic of laser shock that can form a nano-gradient structure is utilized to control the plastic deformation conditions to refine the grain structure of the coating surface to the submicron or even nanometer scale. On the other hand, the phase deformation nucleus and the growth process dynamics are controlled by the phase change conditions to change the phase distribution for structural refinement. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a flow chart of an embodiment of a method for regulating element desorption at a PVD coating interface by laser shock in the present application;
[0029] Figure 2 for Figure 1 A schematic flow chart of an embodiment of step S1 in FIG.
[0030] Figure 3 for Figure 1 A schematic flow chart of an embodiment of step S2 in FIG.
[0031] Figure 4 for Figure 1 A schematic flow chart of an embodiment of step S3 in FIG.
[0032] Figure 5 This is a diagram of a TC4 titanium alloy sample deposited with an AlCrN coating in accordance with an embodiment of a method for regulating and controlling the elemental desorption at a heterogeneous laser shock interface of a PVD coating of the present application;
[0033] Figure 6 This is a surface image of a sample after laser shock treatment according to an embodiment of a method for regulating elemental permeation at a heterogeneous laser shock interface of a PVD coating of the present application;
[0034] Figure 7 This is a cross-sectional morphology of a sample without shock element permeation control according to an embodiment of a method for controlling element permeation at a heterogeneous laser shock interface of a PVD coating of the present application;
[0035] Figure 8 It is an element distribution diagram of the cross section of a sample without shock desorption control in an embodiment of the method for controlling element desorption at the interface of a PVD coating according to the present application;
[0036] Fig. 9This is a cross-sectional morphology diagram of a sample after shock-induced elemental infiltration regulation in an embodiment of a method for regulating heterogeneous laser shock-induced elemental infiltration at a PVD coating interface of the present application;
[0037] Fig.10 This is a diagram of the element distribution of the sample cross section after shock shock shock control of an embodiment of the method for regulating heterogeneous element shock at the PVD coating interface of the present application. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0040] See also Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for regulating the elemental permeation at the interface of a PVD coating by laser shock in the present application. The method comprises the following steps:
[0041] Step S1: pre-treat the substrate based on the size of the substrate.
[0042] Specifically, the size of the alloy substrate is confirmed and the substrate is pre-treated.
[0043] See also Figure 2 , Figure 2 for Figure 1 A flow chart of an embodiment of step S1 in FIG. 1 is a flow chart of an embodiment of step S1 in FIG. 1 . Step S1 includes:
[0044] Step S11. Based on the size of the substrate, perform wire cutting on the substrate to obtain a unit substrate.
[0045] Specifically, a suitable alloy is selected as the base material, such as TC4 titanium alloy, and is processed into a unit alloy block of a fixed size by wire cutting or the like.
[0046] Step S12: Based on the unit substrate and sandpapers of different mesh sizes, the unit substrate is polished step by step.
[0047] Specifically, sandpaper with different mesh sizes is selected to grind each unit alloy block step by step.
[0048] Step S13: ultrasonically clean the unit substrate using ethanol to obtain a pre-treated substrate.
[0049] The unit alloy block is placed in anhydrous ethanol for ultrasonic cleaning and air-dried to obtain a pretreated alloy block.
[0050] Step S2: Based on the pretreated substrate, a PVD coating is prepared on the pretreated substrate.
[0051] Specifically, read Figure 3 , Figure 3 for Figure 1 The method of step S2 includes:
[0052] Step S21 . Based on the pre-treated substrate, arc ion plating and target materials are selected, and the pre-treated substrate and target materials are placed in the sample chamber.
[0053] Specifically, suitable arc ion plating equipment and suitable target materials are selected, wherein the target materials can be pure Al and pure Cr targets.
[0054] Step S22: regulating the vacuum degree of the sample chamber and determining arc bombardment cleaning parameters.
[0055] Specifically, the target material and the substrate are installed at corresponding positions of the sample chamber respectively, and the vacuum pressure in the sample chamber is adjusted, and then the arc light bombardment cleaning parameters are adjusted to preset values.
[0056] Step S23: Introduce deposition gas into the sample chamber, control the proportional flow rate and deposition time of the deposition gas, and obtain a PVD coating.
[0057] Specifically, the ratio of multiple deposition gases is controlled and then introduced into the sample chamber, and after a certain period of time, a PVD coating is deposited on the surface of the pretreated alloy block. The thickness of the PVD coating is 3 to 5 μm (for example, 3 μm, 4 μm, 5 μm); the vacuum degree of the sample chamber is less than 7×10 -3 Pa (e.g. 6.5×10 -3 Pa,6×10 -3 Pa,5×10 -3 Pa).
[0058] Step S24: Based on the deposited PVD coating, the pre-treated substrate is placed in a vacuum and heat treatment environment, and the stress of the PVD coating is eliminated.
[0059] Specifically, the deposited PVD coating is placed at a preset temperature of 600°C, wherein the heating rate does not exceed 7°C / min, the holding time is about 4 hours, and then the furnace is cooled; the vacuum environment is less than 7×10 -3 Pa, thereby eliminating the stress of the PVD coating and making the coating reach a certain thickness.
[0060] Step S3: Based on the parameters of the PVD coating, the parameters of the laser shock are determined, and the PVD coating is subjected to laser shock peening treatment.
[0061] For details, see Figure 4 , Figure 4 for Figure 1 The method of step S3 includes:
[0062] Step S31. Based on the laser equivalent peak pressure, select corresponding laser shock parameters; wherein the laser shock parameters include laser energy, spot diameter and pulse width, etc.
[0063] Specifically, the appropriate laser equivalent peak pressure is determined, and the corresponding laser shock parameters are selected, including laser energy, spot diameter, pulse width, etc.
[0064] Step S32: Based on the selected laser shock area and laser shock range, the PVD coating is laser shocked.
[0065] Specifically, a laser shock region and a shock range are selected, optical glass (such as K9 glass) is used as a constraint layer of the laser shock strengthening region, and the laser shock strengthening is performed in the laser shock strengthening range without an absorption layer. The overlap rate of laser shock strengthening is not less than 50% (such as 50%, 60%, 70% and 80%).
[0066] Step S4. Based on the PVD coating after the laser shock peening treatment, SEM and EDS characterization observations are performed on the PVD coating.
[0067] Specifically, a scanning electron microscope (SEM) was used to observe the surface and cross-sectional morphologies of the PVD coating before and after the laser shock treatment, and the coating thickness was measured based on the cross-sectional morphology.
[0068] The element distribution of the coating and substrate cross section was observed using an X-ray spectrometer to obtain the atomic percentage and distribution of each element.
[0069] Example 1
[0070] The method for regulating the elemental permeation at the interface of a PVD coating by laser shock includes the following steps:
[0071] 1.1 Sample treatment before coating deposition: The substrate material was TC4 titanium alloy, which was processed into a 30mm×30mm×5mm titanium alloy block by wire cutting, and then polished step by step using 80# to 2500# sandpaper, and then ultrasonically cleaned with ethanol and air-dried;
[0072] 1.2 Coating preparation: TC4 titanium alloy was ultrasonically cleaned with anhydrous ethanol and the process was carried out on an MIP-8-800 arc ion plating equipment. The targets were Al and Cr targets with a purity of 99.99%. The targets and substrates were installed in the corresponding positions of the sample chamber. When the vacuum pressure in the sample chamber was less than 7×10 -3After the pressure reached 0.2 Pa, Ar gas was introduced to 0.2 Pa; the arc bombardment cleaning parameters were set to -800 V, 3 min and -600 V, 2 min; N2 was introduced, and the flow ratio of N2 and Ar was controlled to be 1:1, and the Al CrN layer was deposited for 90 min.
[0073] like Figure 5 As shown, Figure 5 The TC4 titanium alloy sample with AlCrN coating is shown in Figure 1. After the deposition, the sample was subjected to diffusion annealing process, kept at 600℃ in vacuum for 4h, and the coating thickness was about 3μm.
[0074] 2. Set up the laser shock control experiment.
[0075] Experimental group: Al CrN coating was deposited on the surface of TC4 titanium alloy; no black tape absorption layer was used during impact, and the impact energy was selected as 0.5J, 1J, and 1.5J respectively;
[0076] Control group: Al CrN coating was deposited on the surface of TC4 titanium alloy; no laser shock treatment was performed;
[0077] 2.1 As Figure 6 As shown, Figure 6 This is the surface image of the sample after laser shock treatment. Determine the parameters of laser shock and perform laser shock treatment: The laser shock equipment uses Nd:YAG laser, and the laser power density is determined according to the laser energy, spot diameter and pulse width. The formula is as follows:
[0078] Laser power density = output power / spot area;
[0079] Among them, peak output power = unit pulse energy / pulse width; the unit pulse energy spot diameter is 2mm, the pulse width is 9ns, and the repetition frequency is 5Hz.
[0080] 2.2 Impact area selection area is 10mm×10mm, and the spot overlap rate is 50%.
[0081] 2.3 Use flowing water with a thickness of 1 to 2 mm as the constraint layer, and do not use a protective layer.
[0082] 3.1 As Figure 7-10 As shown, Figure 7 This is the cross-sectional morphology of the sample without impact infiltration control; Figure 8 This is the element distribution diagram of the cross section of the sample without shock infiltration control; Fig. 9 This is the cross-sectional morphology of the sample after impact infiltration control; Fig.10 This is the element distribution diagram of the sample cross section after impact infiltration control.
[0083] Observation of the results of permeation control: First, the surface and cross-sectional morphologies of the AlCrN coating before and after laser shock treatment were observed using a scanning electron microscope (SEM), and the coating thickness was measured based on the cross-sectional morphology.
[0084] 3.2 Use X-ray energy spectrometer to observe the element distribution of coating and substrate cross section to obtain the atomic percentage and distribution of each element.
[0085] In summary, the present application studies the regulation of element diffusion and penetration of heterogeneous laser shock on the interface of PVD coating on alloy surface based on the principle of laser shock strengthening. In the absence of the protection of the absorption layer, the high temperature, ultra-high-speed stress and strain, and induced crystal defects generated during the laser shock strengthening process are utilized to promote the diffusion and penetration of coating elements on the substrate surface on the basis of the plastic flow mechanism of laser shock strengthening, and to enrich and distribute them to a certain extent, forming a certain gradient element distribution layer. In addition, laser shock strengthening optimizes the interface bonding performance of PVD coating from the aspects of mechanical and metallurgical bonding. On the one hand, the characteristic of laser shock that can form a nano-gradient structure is utilized to control the plastic deformation conditions to refine the grain structure of the coating surface to submicron or even nanometer scale. On the other hand, the phase transformation conditions are used to control the phase deformation nucleus and the growth process dynamics to change the phase distribution for structural refinement. In short, the membrane substrate structure of laser shock strengthening without a protective layer will affect the gradient of the nanostructure, element distribution, and phase distribution of the membrane substrate interface, providing a method for regulating element diffusion and penetration of heterogeneous laser shock on the interface of PVD coating, and providing a new idea for laser shock surface strengthening technology.
[0086] The above description is only an embodiment of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for regulating the elemental permeation at the interface of a PVD coating by laser shock, characterized in that: The following steps are involved: Based on the size of the substrate, the substrate is subjected to wire cutting to obtain a unit substrate, wherein the substrate is TC4 titanium alloy and has a size of 30 mm×30 mm×5 mm; Based on the unit substrate and sandpapers of different meshes, the unit substrate is polished step by step, wherein the mesh of the sandpaper is 80# to 2500#; Performing ultrasonic cleaning on the unit substrate based on ethanol to obtain a pretreated substrate; Based on the pretreated substrate, arc ion plating and target materials are selected, wherein the target materials are Al target and Cr target with a purity of 99.99%, and the pretreated substrate and the target materials are placed in a sample chamber; The vacuum degree of the sample chamber is regulated to be less than 7×10 -3 Pa, introduce argon gas to 0.2Pa, and determine the arc bombardment cleaning parameters; Nitrogen gas is introduced into the sample chamber, the flow ratio of the nitrogen gas to the argon gas is controlled to be 1:1, the deposition time is 90 minutes, and a PVD coating with a thickness of 3 μm is obtained, wherein the PVD coating is an AlCrN layer; Based on the PVD coating, placing the pretreated substrate in a vacuum and 600° C. heat treatment environment, and eliminating the stress of the PVD coating; The PVD coating is subjected to laser shock peening treatment without an absorption layer, and the laser shock energy is selected to be 0.5J, 1J, and 1.5J respectively; Before laser shock peening the PVD coating, the following steps are included: The flowing water with a thickness of 1 to 2 mm is used as the constraining layer of the laser shock peening treatment.
2. The method according to claim 1, characterized in that The laser shock peening method comprises: Based on the laser equivalent peak pressure, corresponding laser shock parameters are selected; wherein the laser shock parameters include laser energy, spot diameter and pulse width; The PVD coating is laser shocked based on the selected laser shock area.
3. The method according to claim 1, characterized in that The overlap rate of the laser shock peening is 50%.
Citation Information
Patent Citations
Method of treating coated cutting tool
CN114222643A